THE ANALYSIS OF SAVINGS BEHAVIOR ON BANKS LISTED IN IDX BEFORE COVID-19 ERA AND DURING COVID-19 ERA - Yosepha Hartana; Frederik G. Worang; Hizkia H. D. Tasik (Universitas Sam Ratulangi, 2023)
This study aims to identify the changes in people’s saving behavior before Covid-19 outbreak and during Covid-19 outbreak. This is why management is crucial to follow the importance of money because, without management skills, money waste will occur and lead to poverty. One of many ways in money management is savings behavior. Saving has many benefits, one of which is preparing an emergency fund for unusual situations, such as current situation of Indonesia and the world that are experiencing the Covid-19 pandemic. This study uses a quantitative approach. Secondary data collected from the bank's Annual Reports during 2018-2021 is analyzed using the Normality Test and Wilcoxon Test, with the sample of 21 banks listed in the Indonesia Stock Exchange (IDX). Keywords: savings, savings behavior, deposit, current account, Net Interest Margin, credit given, non-interest income